Realization of a Half Metal with a Record‐High Curie Temperature in Perovskite Oxides (Adv. Mater. 17/2022). Issue 17 (27th April 2022) - Liu, Zhehong; Zhang, Shuaikang; Wang, Xiao; Ye, Xubin; Qin, Shijun; Shen, Xudong; Lu, Dabiao; Dai, Jianhong; Cao, Yingying; Chen, Kai; Radu, Florin; Wu, Wen‐Bin; et al.
Abstract : Half Metals In article number 2200626, Yi‐feng Yang, Youwen Long, and co‐workers report a new half metal synthesized by a unique high‐pressure and high‐temperature method. The compound exhibits a record‐high Curie temperature up to 710 K in perovskite oxides combined with a wide spin‐up energy bandgap and large saturated moment. The superior synthetic performance makes it promising for spintronic applications.